INVESTIGATING THE INTERPLAY: UNRAVELLING THE IL-6 CONNECTION AND INTRAVENOUS METHYLPREDNISOLONE'S IMPACT ON RECTUS MUSCLE IN THYROID EYE DISEASE: Oral Presentation - Observational Study - Resident - Rangga Athallah Fajar (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Intravenous corticosteroid has been used in management of Thyroid Eye Diseases (TED). Many previous studies have shown the therapeutic benefits of corticosteroid therapy. Recently, the efficacy of high-dose intravenous corticosteroid pulse therapy has been reported. Recent studies have highlighted the potential role of interleukin-6 (IL-6) in the pathogenesis of TED. However, the correlation between IL-6 levels and the effects of IVMP on rectus muscles in patients with TED remains unclear. This study aims to investigate the correlation between IL-6 levels and the effects of IVMP on rectus muscles in patients with TED Methods : Retrospective analysis were used in the data collection of patients with active Thyroid Eye Disease who undergone high-dose intravenous methylprednisolone pulse therapy (500mg per week for 6 successive weeks) at Sardjito General Hospital between January 2022 and December 2022. Data on the Level of IL-6 were obtained at the start of treatment, and quantitative computed tomography (CT) of the orbit and were performed before and after treatments. Demographics data were presented in tables and graphs. Results : This study included 62 eyes of 31 patients (61,3% female) with mean age of 37.8+13.47 years old. There was significant inverse correlation in levels of IL-6 and ?SR (P=0.037) which implies a reduced effect of IVMP on SR. However, other statistical analyses on different rectus muscle groups bare no statistical significance. Conclusion : The use of IL-6 as a single predictor of responsiveness of the treatment of high dose intravenous methylprednisolone is not endorsed by the result of this study. However, further studies with better established level of IL-6 both pre and post treatment, and more inclusive parameters are needed to better provide better understanding on the role of IL-6.